On the Role of Eddy Mixing in the Subtropical Ocean Circulation - Liu, Tongya; Ou, Hsien-Wang; Liu, Xiaohui; Chen, Dake (Frontiers in Marine Science, 2022)
Most of the classic wind-driven circulation theories based on Sverdrup balance have neglected the profound influence of eddy mixing on the large-scale potential vorticity (PV) distribution, thus failing to explain some prominent features of the observed circulation. In this study, using a series of numerical experiments based on the MITgcm, we diagnose the PV balance to quantify the effect of eddy mixing on the subtropical gyre. Four horizontal grid-spacings of 1°, 1/3.2°, 1/10°, and 1/32° are selected to compare the structure of the upper-ocean circulation to examine the effect of different eddy influences. In the 1° grid case, the thermocline structure is as predicted by the Sverdrup dynamics, with its maximum depth located in the subtropical interior where the wind stress curl is strongest. With increasing resolution, however, this maximum depth is displaced towards the subtropical front, which more closely resembles the observed thermocline. From 1° to 1/32°, the enhanced eddy mixing tends to homogenize the macroscopic PV in the subtropical gyre and reduces the meridional PV range by about 75% of the non-eddy (1°) solution; and the region where Sverdrup balance holds is relegated to isolated patches, with its area reduced by about 60%. Furthermore, sensitivity experiments show that the observed thermocline structure is well reproduced in eddy-resolving runs, indicating that the PV mixing provides a reasonable explanation of the subtropical circulation. Our results suggest that the Sverdrup relationship should be treated carefully in the eddy-rich region, even in the subtropical interior.